2018
DOI: 10.1002/ange.201807069
|View full text |Cite
|
Sign up to set email alerts
|

Highly Diastereo‐ and Enantioselective Synthesis of Cyclohepta[b]indoles by Chiral‐Phosphoric‐Acid‐Catalyzed (4+3) Cycloaddition

Abstract: Ah ighly enantio-and diastereoselective formal (4+ +3) cycloaddition of 1,3-diene-1-carbamates with 3-indolylmethanols in the presence of achiral phosphoric acid catalyst is reported. The approachd escribed herein provides efficient access to 6-aminotetrahydrocyclohepta [b]indoles in good yields with mostly complete diastereoselectivity and excellent levels of enantioselectivity (> 98:2 dr and up to 98 %ee). Mild reaction conditions,facile scale-up,and versatile derivatization highlight the practicality of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 97 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…41 Subsequently, the same group extended this concept to phosphoric acid catalyzed [3+4]-cycloadditions with 1-amino-substituted 1,3-butadienes 59 , which delivered cyclohepta[ b ]indoles 60 in good yields and with excellent stereocontrol as well. 42 Control experiments and the isolation of reaction intermediates suggested a stepwise reaction pathway in both cases, comprising an initial conjugate addition followed by cyclization from the indole-2-carbon. This mechanistic picture suggested that 2-alkylindoles might deviate from this pathway and cyclize from the more nucleophilic and more readily accessible indole-3-carbon atom leading to spiro­cyclic indolenines.…”
Section: Cycloadditions Of Indolyl-3-methidesmentioning
confidence: 99%
“…41 Subsequently, the same group extended this concept to phosphoric acid catalyzed [3+4]-cycloadditions with 1-amino-substituted 1,3-butadienes 59 , which delivered cyclohepta[ b ]indoles 60 in good yields and with excellent stereocontrol as well. 42 Control experiments and the isolation of reaction intermediates suggested a stepwise reaction pathway in both cases, comprising an initial conjugate addition followed by cyclization from the indole-2-carbon. This mechanistic picture suggested that 2-alkylindoles might deviate from this pathway and cyclize from the more nucleophilic and more readily accessible indole-3-carbon atom leading to spiro­cyclic indolenines.…”
Section: Cycloadditions Of Indolyl-3-methidesmentioning
confidence: 99%
“…[23] In 11). [25] In the event, substituted indolyl methanols 36 reacted with Cbz-protected dienamines 37 in the presence of the chiral phosphoric acid TRIP (À )-38.…”
Section: (4 + 3) Cycloadditionsmentioning
confidence: 99%
“…reported the synthesis of substituted non‐racemic cyclohepta[ b ]indoles 39 by organocatalytic intermolecular (4+3) cycloaddition (Figure 11). [25] In the event, substituted indolyl methanols 36 reacted with Cbz‐protected dienamines 37 in the presence of the chiral phosphoric acid TRIP (−)‐ 38 .…”
Section: Cyclohepta[b]indoles From Indolesmentioning
confidence: 99%
“… 5 The most representative and versatile protocols involve (4 + 3) 6 cycloadditions ( Scheme 1 ) and were developed, beyond the examples reported by Gaich and Stempel, also in their enantioselective version. 7 …”
Section: Introductionmentioning
confidence: 99%
“…5 The most representative and versatile protocols involve (4 + 3) 6 cycloadditions (Scheme 1) and were developed, beyond the examples reported by Gaich and Stempel, also in their enantioselective version. 7 In these cycloaddition reactions, the indolyl moiety functions as the 3C partner, whereas (4 + 3) cycloaddition reactions having indoles as the 4C component have become operative only more recently (Scheme 2). 8 For example, in 2017, Zhang and co-workers reported a regioselective gold-catalyzed (4 + 3) cascade cycloaddition/ CH functionalization of 2-vinylindoles and propargylic esters leading to highly substituted derivatives.…”
Section: ■ Introductionmentioning
confidence: 99%